Effect of Dietary Lead Exposure on Hematological Parameters and Their Alleviation by Antioxidants in Broilers - Jaiswal, Ritesh; Ali, S. L.; Roy, S.; Dinani, O. P.; Jaiswal, Sudhir Kumar (International Journal of Bio-resource and Stress Management, 2023)
A total number of 126 day old broiler chicks were randomly assigned into 6 treatments groups A, B, C, D, E and F. The birds of group A were kept as control, while group B received lead acetate @ 200 mg kg-1 alone, whereas, birds of group C, D, E and F received Lead acetate @ 200 mg kg-1+Ascorbic acid @ 200 mg kg-1, lead acetate @ 200 mg kg-1 along with α-tocopherol @ 100 mg kg-1+Selenium @ 0.1 mg kg-1, Lead acetate @ 200 mg kg-1+DL-methionine @ 100 mg kg-1 and Lead acetate @ 200 mg kg-1+methanolic extract of Cissus quadrangularis (CQE) @ 400 mg kg-1 respectively. In group-B TEC, hemoglobin and MCV declined significantly (p<0.05) as compared to control on day 21. At day 42 significant (p<0.05) decrease in Hb, PCV and MCV was recorded in lead treated group. Treatment with Vit-E and Se (group-D) was found effective in restoration of TEC and Hb. Evaluation of leucocyte parameters revealed no significant (p<0.05) difference in total and differential leucocytic count on day 21 and 42. However, significant (p<0.05) increase in lymphocyte count was recorded in lead exposed group as compared to other groups. Vit-E @ 100 mg kg-1 and Se @ 0.1 mg kg-1 having highest efficacy against lead intoxication followed by Vitamin-C @ 200 mg kg-1, DL-methionine @ 100 mg kg-1 and methanolic extract of CQE @ 400 mg kg-1 to alleviate lead toxicosis upto the level of 200 mg kg-1 in broiler diet.